下顎臼後部に生じた乳頭状唾液腺腺腫の1例 - 片岡, 良浩; 江副, 祐史; 熊本, 裕行; 野上, 晋之介; 高橋, 哲; 齋藤, 悠 (日本口腔外科学会雑誌, 2019)
We report a case of sialadenoma papilliferum arising in the left retromolar region. An 81-year-old woman visited our hospital with a chief complaint of an oral mass in the left retromolar region, which was found to be elastic, soft, and papillary on palpation and measured 12 × 7 mm. The tumor was removed with the patient under general anesthesia, and the excised specimen was histologically diagnosed as sialadenoma papilliferum. Laboratory test results showed that squamous cells were immunoreactive for AE1/AE3, EMA, CEA, p40, p63, and Ki-67. Luminal cells within the ductal structures positively stained for CK7, EMA, and S-100, whereas no staining for CEA or α- SMA was noted. Basal cells within the ductal structures were immunoreactive for CK5/6, 7, CAM5.2, p40, and p63, while the reactivity of myoepithelial cells was not specific. The postoperative course of the patient was uneventful, and no recurrence was detected on a follow-up examination performed 2 years 9 months after surgery.